STRATEGI DAN TANTANGAN SISWA DALAM MENINGKATKAN KEMAMPUAN BERBICARA: STUDI KASUS SEKOLAH MENENGAH KEJURUAN 1 RENGAT - Nida Ulfadila; Afrianto '; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at investigating students’ strategies and challenges in improving speaking ability in a context of Vocational High School 1 Rengat. This case study employed combining quantitative and qualitative research methods. There were 27 students of Vocational High School 1 Rengat chosen as participants of this study. All of them was asked to fill in a survey of the questionnaires, then 10 out of 27 students were randomly selected to have semi-structured interviews. The results of the study showed that students of Vocational High School 1 Rengat have some challenges in improving speaking ability. Based on the data from questionnaires and semi-structured interviews, it was found that most participants (99,3%) are lack of grammar mastery, some others (74,8%) choose to speak a local language in learning process, and (68,1%) feel nervous when they are asked to speak English. Then, at the same time, they also have some strategies in improving speaking ability. The results show that an interesting topic that is given by the teacher is the one of strategies that is needed by the students (78,6%), and other participants show that (71,1%) find partner as the next strategy that is needed by the students. Meanwhile, at the next strategy (69,6%) participants likes to listen to western music to improving their speaking ability.